Sseken For Acne : Serum Bunga Kenangan Untuk Kulit Berjerawat - oktavia Ronita, shella (Journal of Beauty and Cosmetology (JBC), 2021)
Acne is a skin disorder associated with the production of excess oil (sebum). Acne occurs when hair follicles or where hair grows are clogged with oil and dead skin cell. Ylang flowers are often used by people as home garden decorations. In addition to decoration, ylang flowers can also be used as traditional medicine. In the past, parents used ylang flowers to treat coughs, treat malaria, shortness of breath, and ingredients to make herbal medicine for mothers who had just given birth. Ylang ylang can produce essential oil, ylang ylang essential oil is used as raw material for the bath soap, perfume and cosmetics industries. Ylang flower extract contains linalool, geraniol, safrol, cadinene, pinene eugenol, benzoic acid, geraniol, and farsenol which are able to nourish the skin so that it is more moist, giving elasticity to the skin thereby reducing wrinkles and fine lines on the face. One of the other benefits of ylang flower essential oil is for acne recovery. That's why we made "Sseken for Acne". Serum containing ylang flower which is useful for curing acne, moisturizing the skin and reducing fine lines, signs of aging or anti-aging. Keywords: Acne; Serum; Ylang flower